Analysis of Software Requirement Management Results for Physical Tests of Adolescent Pencak Silat Fighting Categories - Deny Pradana Saputro; Muhammad Riski Adi Wijaya; Muhammad Fadli Dongoran (STKIP Muhammadiyah Kuningan, 2020)
Management of physical test result for adolescent pencak silat category in the current state is done manually so that it is prone to make errors and takes a long time which causes the data processing of test results to be less effective and efficient. This study aims to determine the needs of trainers for software to managing the physical results of adolescent pencak silat fighting category. The research method used is descriptive. Subjects involved in this study amounted to 6 trainers with certified trainer criteria, had accompanied competing athletes and academics who possessed theoretical and practical pencak silat knowledge. Data collection using was a questionnaire. Data analysis used descriptive statistics. The results of this study show that: the trainer had held physical exercises and physical tests for pencak silat. Physical tests conducted use the composition of adolescent pencak silat test match category. To run a simple test process, a physical pencak silat physical test guide is needed, together with norms for the assessment of test results. The results of physical tests that have been carried out are used to evaluate physical conditions and determine the training program. In order for the process of managing physical test results to be more effective and efficient, it is necessary to obtain the software for processing the results of adolescent pencak silat physical tests in match category. The conclusion of this research is there is a need of software for managing the physical test results of adolescent pencak silat in the fighting category.